Work-related medical surveillance in small workplaces. - Tolonen, Matti; Hassi, Juhani; Vaaranen, Anika; Kolivuori, Terttu; Heikkilä, Pirjo; Hietanen, Maila; Kakko, Kauno; Yrjänheikki, Erkki (Scandinavian Journal of Work, Environment & Health, 1979)
This paper discusses job-related health examinations only; general screening for health is the responsibility of the community and therefore beyond the scope of occupational health services. Accordingly, in this context health examinations were considered sensible for two reasons only: first, to insure that an employee`s mental and physical attributes match the requirements of his or her job and, second, to detect possible adverse health effects caused by work. The first category refers to preemployment examinations and the second to periodic examinations. A routine preemployment physical examination program for workers considered for any job seems needless from a labor protection point of view. One-third of the work force under study was considered to be in need of either preemployment or periodic health examinations or both. Young workers (under the age of 18) to be examined prior to assignment to a new job constituted only 2 Ofo of the population. Most preemployment and periodic examinations were required for workers exposed to noise. They numbered 480 (20%). Eighty-five of them should be given an audiometry examination annually and the rest, 395 persons, every third year. Exposure to chemical substances created a need for health examinations for less than 10 % of the workers, allergens, solvents, mineral dusts, and metals being the most common such substances. In eight establishments 25 persons were exposed to lead. Their blood tests indicated, however, that routine health monitoring was unnecessary. In addition, truck driver examinations and color vision tests for electricians could fit within occupational health care, along with the preemployment examinations of food handlers required by the National Health Law. In contrast to engineering controls, the training of proprietors of small businesses and their employees, labor inspection, and other preventive measures, health examinations seem to play a secondary role in the labor protection of small workplaces.
Keywords: health examination; medical surveillance; occupational health; small enterprise; small workplace; work-related medical surveillance